Construction of public health core competence and the improvement of its legal guarantee in China - Huang, Lansong; Yu, Qinglin; Wang, Quansheng (Frontiers in Public Health, 2023)
Public health core capacity, first established by the 58th United Nations General Assembly in 2003 and recognized by the World Health Organization when “the International Health Regulations” were revised, refers to the basic and necessary capacity to allocate human, financial, and material resources for the prevention and control of public health events that a country or region should have. It includes national and regional levels, and its constituent elements and their basic requirements differ, but public health core capacity building at both national and regional levels requires certain legal safeguards. At present, there are still some problems, including the imperfect legal system, conflicting legal norms, the non-sufficient supply of local legislation, and the weak operability of legislation in the legal guarantee of public health core capacity building in China. China should make improvements in terms of comprehensive cleaning of existing public health laws, strengthening their post-legislative evaluation, adopting parcel legislation, strengthening legislation in key areas of public health, and promoting the supply of local legislation. The goal is to provide a perfect and comprehensive legal system to guarantee the construction of China's core capacity in public health.